2017
DOI: 10.14744/nci.2017.79847
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Of Relationship Between Femoro-Tibial Angle And Meniscus Injury

Abstract: OBJECTIVE:The purpose of this study was to assess the relationship between the presence of meniscal injury and the femorotibial angle in the knee joint.METHODS:Patients who underwent knee magnetic resonance imaging (MRI) at our department between January 2015 and March 2015 were included in this study. Knee MR images of these patients were retrospectively re-evaluated for meniscal injury. The anatomic femorotibial angle measurements of the patients were calculated using AP knee radiograms. The relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…This was not statistically significant (p>0.01). Sirik (3) reported that the mean FTA value was 6.1±1.50°C in the knee joints with a LM injury and 5.6±1.96°C in the normal knee joints. This was not statistically significant (p=0.20).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This was not statistically significant (p>0.01). Sirik (3) reported that the mean FTA value was 6.1±1.50°C in the knee joints with a LM injury and 5.6±1.96°C in the normal knee joints. This was not statistically significant (p=0.20).…”
Section: Discussionmentioning
confidence: 99%
“…MRI is the most accurate and least invasive method for diagnosing meniscal lesions. In addition, soft tissues, articular cartilage, tendon injuries, and ligaments can be evaluated better with an MRI than with other imaging methods (1,3). A normal meniscus is seen as a triangular-shaped low intensity signal on T1-and T2-weighted sequences or on FSE sequences (1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Medial KOA may result from knee alignment disorders or injuries that damages the cartilage and overloads the medial tibiofemoral compartment. 2 Knee malalignment has been suggested as an important biomechanical risk factor in KOA progression and declines in physical function. 3,4 Both high tibial osteotomy (HTO) and unicompartmental knee arthroplasty (UKA) are most frequently used medial KOA joint surgeries.…”
Section: Introductionmentioning
confidence: 99%